ASUHAN KEPERAWATAN ANAK THALASEMIA DENGAN DIAGNOSA PRIORITAS KETIDAKEFEKTIFAN PERFUSI JARINGAN PERIFER - Ana Farida Ulfa; Edi Wibowo (Jurnal EDUNursing, 2017)
Abstract  Thalassemia is a chronic descent disease, where clients with thalassemia will experience a continuous decrease in Hb. This condition causes thalassemia clients to undergo regular hospitalization to obtain blood transfusions. Currently, tansfusion is the best treatment of thalassemia.This research uses qualitative method with case study approach. The researcher chose the research sample with the sampling quota. Researchers perform nursing care on 2 clients thalasemia who are undergoing inpatient at RSUD Jombang.The results show that the priority problem in thalassemia clients is peripheral tissue perfusion ineffectiveness. This problem occurs because the decrease in client Hb levels that cause oxygen supply to the entire body tissue is disrupted. The examination results on both clients showed low Hb levels. Implementations performed for both clients are: observation of vital signs, including capillary refill observation (CRT), blood transfusion administration, nutrition and activity settings. The results of evaluation on clients 1 and 2 found that in addition to transfusion of nutrition and activity management is also very necessary in clients with thalassemia, so it is important that health education given to his family Keywords: nursing care, thalassemia, peripheral tissue perfusion effectiveness